Agreement between fat-free mass from bioelectrical impedance analysis and dual-energy X-ray absorptiometry and their use in estimating resting metabolic rate in resistance-trained men - Alex S. Ribeiro; Sandro L. Sofiati; Witalo Kassiano; Diogo V. Martinho; Matheus A. Nascimento; Ademar Avelar; Michele C. C. Trindade; Jerry L. Mayhew; Edilson S. Cyrino (Journal of the International Society of Sports Nutrition)
Background This study aimed to determine the agreement between fat-free mass (FFM) estimates from bioelectrical impedance analysis (BIA) and dual-energy X-ray absorptiometry (DXA) and their use in estimating resting metabolic rate (RMR) in men undergoing resistance training.Methods Thirty healthy resistance-trained men (22.7 ± 4.4 years, 70.0 ± 8.7 kg, 174.6 ± 6.7 cm, and 22.9 ± 2.3 kg/m2) were evaluated. The equation developed by Tinsley et al. (RMR = 25.9 × fat-free mass [FFM] + 284) was adopted to calculate the RMR. DXA was used as the reference method for FFM.Results Furthermore, FFM was also estimated by BIA using a spectral device. No significant difference (p > 0.05) was observed between DXA (1884.2 ± 145.5 kcal) and BIA (1849.4 ± 167.7 kcal) to estimate RMR. A positive and significant correlation (r = 0.89, p < 0.05) was observed between DXA and BIA estimates of RMR. The mean difference between methods indicated that BIA presented a bias of −34.8 kcal.Conclusion These findings suggest that using FFM derived from DXA or BIA results in similar RMR estimates in resistance-trained men.